2016
DOI: 10.1016/j.jclepro.2015.04.086
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance of Wood-Polymer Composites: a conjoint analytical approach with a focus on innovative and environmentally concerned consumers

Abstract: a b s t r a c tWood-Polymer Composites (WPCs) can contribute towards resource efficiency as they mainly consist of wood by-products and/or waste materials. The eco-innovative materials represent a hybrid solution on the 'two-evils' continuum' constituted by the competing materials of wood and plastics; the former being too expensive and resource consuming in mass consumption, the latter cheap but environmentally hazardous. However, consumer acceptance of WPCs is questioned due to the merger of components consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 61 publications
2
38
0
6
Order By: Relevance
“…Thus, hypothesis H6 "Higher innovation-friendly increases consumers' preferences for a high percentage of bioplastic in the fabric of bio-based apparel" is supported. This result is in line with previous studies showing that consumer innovativeness promotes the adoption of innovative green products [13,59,62].…”
Section: Influences Of the Covariatessupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, hypothesis H6 "Higher innovation-friendly increases consumers' preferences for a high percentage of bioplastic in the fabric of bio-based apparel" is supported. This result is in line with previous studies showing that consumer innovativeness promotes the adoption of innovative green products [13,59,62].…”
Section: Influences Of the Covariatessupporting
confidence: 93%
“…Innovation-friendly: Consumers' innovativeness is also an important driver for the adoption of environmentally friendly product innovations, as found by Tellis et al [59], Rahman et al [60] and Jansson [61]. Recently, Osburg et al [62] showed that choices for wood-plastic composites over conventional plastics correlated with the respondents' innovativeness. Furthermore, Scherer et al [13] revealed that ecologically sensitive respondents are more innovative.…”
Section: Hypothesis 5b (H5b)mentioning
confidence: 95%
“…Wood plastic composites (WPCs) are an eco‐innovative material mainly consisting of post‐consumer recycled wood and plastic . They are also relatively low‐cost composite materials with superior or comparable performance to traditionally used materials .…”
Section: Introductionmentioning
confidence: 99%
“…It was first developed in 1964 for psychometric studies, and it was used in marketing studies by Green and Rao (). It remains an important research method and has been widely applied in many studies, especially those focusing on products and consumers (e.g., Acosta et al, ; Almli, Øvrum, Hersleth, Almøy, & Næs, ; Arenoe, van der Rest, & Kattuman, ; Bech‐Larsen & Grunert, ; Cai & Aguilar, ; Lima Filho, Della Lucia, Lima, & Minim, ; Lebeau, Macharis, & Van Mierlo, ; Rokka & Uusitalo, ; Osburg, Strack, & Toporowski, ; Zimmermann et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Presuppositions are not necessary in cluster analysis, while it supplies ways to apply post hoc, or cluster‐based segments, and the core idea is to let the data speak for themselves for seeking consumer groups who share common trade‐offs, attitude, preference towards products (Green et al, ). Many market research studies have applied cluster analysis based on the outputs of conjoint analysis—importance and utilities of attributes which construct the preferences—carrying out a post hoc segmentation (Annunziata & Vecchio, ; Claret et al, ; Ferreira, Maia, & Boubeta, ; Font I Furnols et al, ; Kim, Son, & Sohn, ; Lopes, ; Osburg et al, ; Picón, ; Rokka & Uusitalo, ; Wu, Liao, & Chatwuthikrai, ).…”
Section: Methodsmentioning
confidence: 99%